2015
DOI: 10.1097/coc.0b013e3182a790ea
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Factors Associated With Severe Hematological Toxicity in Glioblastoma Patients During Radiation Plus Temozolomide Treatment

Abstract: Although we studied a small population, we suggest that both clinical and genetic factors might simultaneously be associated with severe myelosuppression developed during TMZ plus RT. However, our results deserve validation in larger prospective studies and, if the factors associated with severe myelotoxicity are validated, dose adjustments of TMZ for those patients may reduce the risk of severe myelotoxicity during the concomitant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…Current standard of care includes surgery, systemic temozolomide (TMZ), and radiation. Systemic chemotherapy (SC) is thought to damage the bone marrow (BM) and subsequently affect the number and activation state of resident immune cells (4), raising concerns for potential antagonistic interactions between SC and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Current standard of care includes surgery, systemic temozolomide (TMZ), and radiation. Systemic chemotherapy (SC) is thought to damage the bone marrow (BM) and subsequently affect the number and activation state of resident immune cells (4), raising concerns for potential antagonistic interactions between SC and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…9 At this time, we are continuing to be more conservative with dosing in women, particularly with higher BSA and/or lower creatinine clearance. A prospective series of glioblastoma patients receiving full-dose chemo-radiotherapy and adjuvant chemotherapy found that methylated O6-methyl-guanine-DNA methyltransferase promoter and specific pleomorphic variants of the cytochrome P450 oxidoreductase and methionine adenosyltransferase 1A genes in plasma are independent predictors of thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour-associated myeloid cells contribute significantly to the tumour mass, and have been proposed to promote tumour growth, survival, and invasion of surrounding tissues by producing growth factors, cytokines, and proteolytic enzymes [179,183]. Alkylating agents such as temozolomide (TMZ) are the standard therapy for glioblastoma, and commonly result in profound myelosuppression [184]. …”
Section: Myeloid Cells: the White Knights Of Cns Therapy?mentioning
confidence: 99%